Isolation of atmospheric nitrogen-free fixing bacteria from the endorhizosphere of Helianthus tuberosus and Smallanthus sonchifolius - Di Barbaro, Maria Gabriela (2020)
The objective of the work was to determine the presence of fixing bacteria free of atmospheric nitrogen in the endorhizosphere of topinambur (Helianthus tuberosus) and yacón (Smallanthus sonchifolius), cultivated in the Central Valley of the Province of Catamarca. Roots of each species were collected and the technique proposed by Döbereiner et al. for the isolation of N-free endorrhizospheric fixing bacteriatwo, Azospirillum sp. The isolates obtained were morphologically and physiologically characterized, and three different morphotypes of each plant species were selected for molecular identification.Eleven autochthonous fixative microorganisms free of atmospheric nitrogen present in the endorhizosphere of the crops under study were described, 6 in topinambur and 5 in yacón. All isolates belonging to the genus Pseudomonas. In topinambur, Pseudomonas sihuiensis and in yacón of Pseudomonas alcaligenes, P. resinovorans and P. sihuiensis. The isolation of autochthonous nitrogen-free bacteria native to P. sihuiensis, P. alcaligenes and P. resinovorans is reported for the first time in the endorhizosphere of topinambur (H. tuberosus) and yacón (S. sonchifolius), cultivated in soils of the Central Valley of the Province of Catamarca